Penerapan Arsitektur Feminisme Pada Sekolah Mode (Fashion) di Gorontalo - Nurtiansyah; Ernawati; Syafriyani (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Clothing is no longer viewed solely as one of the basic human needs alongside food and shelter, but also as a form of self and social identity, as well as a reflection of fashion trends and aesthetics. The evolution of fashion is influenced by changes over time, and interest in fashion is not limited to teenagers, but also includes adults—both men and women—and even children. The province of Gorontalo holds great potential to develop as a fashion industry hub, supported by the presence of various shopping centers, both large and small, that offer a wide range of clothing and fashion items. This study aims to design a fashion school that serves as an educational, recreational, and commercial facility related to fashion in Gorontalo, while implementing a feminist architectural approach in both its functional and aesthetic aspects. The design method used is descriptive, incorporating literature studies, collection of primary and secondary data, and field surveys. A comprehensive analysis was conducted on the aspects of site, layout, function, form, circulation, and building systems. The main principles of the feminist architectural approach applied in this design include the use of soft and subtle colors, environmentally friendly materials, and ornamental forms inspired by plants, birds, and flowers, symbolizing feminine qualities. The resulting fashion school design is expected not only to serve as a center for education but also as a space for empowerment, fashion innovation, and comfort for all users.